A low phase noise super–harmonic coupling quadrature VCO using an additional double frequency oscillator. (October 2018) - Jafari, Bahram; Sheikhaei, Samad
Abstract: In this paper, using an additional oscillator that operates at twice the main output frequency, super–harmonic coupling is created between two LC cross–coupled oscillators. The additional oscillator output signals are injected into the two main oscillators in a special way, such that in addition to forcing those oscillators to work in quadrature mode, a tail current shaping technique is performed on them, through the same circuit path. As a result, the main oscillators output phase noise is reduced. The second harmonic signals with the help of two additional NMOS transistors shape the gate voltages and consequently the drain current of the tail transistors. The quadrature mode operation of the proposed circuit is mathematically proved and the intrinsic tail current shaping behavior of it is analyzed. The proposed QVCO is designed in a 0.18 μm CMOS technology with a supply voltage of 1.8 V and a total power consumption of 4.4 mW at 2 GHz center frequency with 5.5% tuning rage. Simulation results confirm the proposed quadrature mode operation. It also shows the phase noise of −128.1 dBc/Hz for the proposed QVCO at 1 MHz offset and 1.92 GHz carrier, which is 9.3 dB better than that of the conventional Parallel (P)–QVCO. The maximum phase error for 0.5% I and Q tank capacitor mismatch is 1.47°. Graphical abstract: